2007
DOI: 10.1148/radiol.2432051246
|View full text |Cite
|
Sign up to set email alerts
|

Inoperable Hepatocellular Carcinoma: Transarterial188Re HDD–Labeled Iodized Oil for Treatment—Prospective Multicenter Clinical Trial

Abstract: TART appears to be a safe, effective, and promising therapeutic option in patients with inoperable HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 19 publications
4
40
2
Order By: Relevance
“…AFP response was classified into the following: (a) complete response (normalization), (b) partial response (decrease by .50% of the baseline value), (c) [19]. The complications of TACE that occurred within 4 weeks were recorded according to CTCAE [17].TTP was defined as the time from the baseline radiological data to disease progression.…”
Section: Assessmentsmentioning
confidence: 99%
“…AFP response was classified into the following: (a) complete response (normalization), (b) partial response (decrease by .50% of the baseline value), (c) [19]. The complications of TACE that occurred within 4 weeks were recorded according to CTCAE [17].TTP was defined as the time from the baseline radiological data to disease progression.…”
Section: Assessmentsmentioning
confidence: 99%
“…a dose escalation study to find the optimum dose has been proposed. 14 two large-scale phase ii studies of 188 re-lipiodol for the treatment of HCC were conducted in developing countries 39,40 and included 93 and 185 patients with advanced disease. Both trials demonstrated that 188 re-lipiodol treatment is feasible and well tolerated.…”
mentioning
confidence: 99%
“…183 In a multicenter trial from India, TART was found to be a safe, effective, and promising therapeutic option in patients with inoperable HCC. 184 However, the availability of Rhennium is a constraint here. Due to logistic limitations and radiation exposure, Yttrium-90 microspheres (Y90) microspheres are currently in use.…”
Section: Role Of Trans-catheter Therapies In Hepatocellular Carcinomamentioning
confidence: 99%